SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN INVESTASI SAHAM SYARIAH DALAM INDEKS JII 70 MENGGUNAKAN METODE AHP BESERTA PERHITUNGAN MONEY MANAGEMENT - Munir, Muhammad Saiful; Rahardiyanto, Panca (SPIRIT, 2023)
Abstract : Stock investment is an investment activity by purchasing a stock in the hope of getting a large enough reward, but it is important to note that stock investment is an activity that has the same risk and reward. Since the Covid-19, the number of single investor identification is increasing, but there are still many novice investors who are confused about which sector to start investing in and which company to choose as an investment as well and how to put capital with their goal. This research is one step to help novice investors find out which companies aresuitable to be chosen using the AHP method, supported by several company financial reports. And this research, the Money Management feature is added to make it easier for investors to allocate the funds they want to invest according to their goals. With the AHP method, the company's financial statements that were previously standardand unstructured have turned into structured and directed so that novice investors who use this application can get a view on choosing the best stock based on the results of the highest ranking value and also the investors with this application get help with money management simulation by prioritizing averaging techniques so that the return they are get can be maximized.